A study on fatigue fracture at double and tapered cantilever beam specimens bonded with aluminum foams. (15th October 2016) - Lee, J.H.; Choi, H.K.; Kim, S.S.; Cho, J.U.; Zhao, G.; Cho, C.; Hui, D.
Abstract: In this study, the models of simple double cantilever beam (DCB) and tapered double cantilever beam (TDCB) were designed to analyze the fracture behavior of the aluminum foam. The fracture behaviors of composite materials exhibit similar trends. The energy release rate increases as the crack length increases and the specimen height decreases. The bonding force influences the adhesive joints of structure. The DCB and TDCB model can be applied generally to the structure with complex configuration. An aluminum foam model has been constructed by using the configuration of DCB and TDCB models in this study. This paper studies the fracture characteristics of specimens due to two kinds of configurations by comparing with the experimental results of DCB and TDCB specimens for mode 1. This study aims to apply fracture toughness to the design of adhesive joints.